Long‐term outcome of anorectal biofeedback for treatment of fecal incontinence. Issue 8 (1st June 2018) - Mazor, Y.; Ejova, A.; Andrews, A.; Jones, M.; Kellow, J.; Malcolm, A.
Abstract: Background: Long‐term outcome data for anorectal biofeedback (BF) for fecal incontinence (FI) is scarce. Our aims were to describe the long‐term symptom profile, quality of life, and need for surgery in FI patients following BF. Methods: One hundred and eight consecutive female patients with FI who completed an instrumented BF course were identified for long‐term follow‐up. In 61 of 89 contactable patients, outcome measures were assessed at short‐term (end of BF), mid‐term (9 months median), and long‐term (7 years median) follow‐up after treatment. Key Results: Long‐term response rate (50% or more reduction in FI episodes/wk compared to before BF and not requiring surgical intervention) was seen in 33/61 (54%) patients. Thirteen of these had complete continence. Improvement was seen at short, mid, and long‐term follow‐up for patients' satisfaction and control of bowel function. In contrast, fecal incontinence severity index and quality of life measures, which improved in short and mid‐term, were no different from baseline by long‐term follow‐up. Patients classified as short‐term responders were far more likely to display a long‐term response compared to short‐term non‐responders (68% vs 18%, P  < .001). Conclusions & Inferences: Long‐term symptom improvement was observed in more than half of FI patients at 7 year post BF follow‐up. Quality of life improvements, however, were not maintained. Patients improving during the initial BF program have a high chance of long‐term improvement, while patients who do not respond to BF should be considered early for other therapies. Abstract : Symptom improvement was seen in over half of patients with fecal incontinence treated with anorectal biofeedback at long‐term follow‐up (median 7 years). Quality of life improvements, however, were not maintained. Patients initially responding to biofeedback treatment can be assured about their good long‐term prognosis, while those who do not respond should be considered early for other therapies.